Examining the factor structure of narrative meaning-making for stressful events and relations with psychological distress. Issue 9 (21st October 2018) - Graci, Matthew E.; Watts, Ashley L.; Fivush, Robyn
ABSTRACT: This study examined the underlying factor structure of 15 narrative meaning-making indices for narratives of stressful events, and explored the incremental validity of the narrative factor solution over and above general personality traits in predicting various indices of psychological well-being. Two-hundred and twenty four undergraduates ( M age = 19.2 years, SDage = 2.1; 114 males and 110 females; 67.6% Caucasian, 12.0% East Asian, 7.6% African-American, 4.0% South Asian, 2.2% Hispanic, and 6.7% as mixed or Other origin) wrote about the most traumatic experience in their life, and completed a series of psychological questionnaires. The narratives were coded in 15 ways theoretically derived from the narrative meaning-making literature. A series of exploratory structural equation models indicated that a four-factor solution best approximated the data. The four factors were: positive processing, negative processing, integrative meaning, and structure. All four factors related differentially to indices of well-being over and above traits. There appear to be four distinct, but related, factors of narrative meaning-making for memories of stressful events, which shed light on the nuanced relations with well-being.